Does the Sign of the Cu-Gd Magnetic Interaction Depend on the Number of Atoms in the Bridge? - Costes, Jean-Pierre; Duhayon, Carine; Mallet-Ladeira, Sonia; Shova, Sergiu; Vendier, Laure (Chemistry : a European journal, 2016)
Several theoretical investigations with CASSCF methods confirm that the magnetic behavior of Cu–Gd complexes can only be reproduced if the 5d Gd orbitals are included in the active space. These orbitals, expected to be unoccupied, do present a low spin density, which is mainly due to a spin polarization effect. This theory is strengthened by the experimental results reported herein. We demonstrate that Cu–Gd complexes characterized by Cu–Gd interactions through single‐oxygen and three‐atom bridges consisting of oxygen, carbon, and nitrogen atoms, present weak ferromagnetic exchange interactions, whereas complexes with bridges made of two atoms, such as the nitrogen–oxygen oximato bridge, are subject to weak antiferromagnetic exchange interactions. Therefore, a bridge with an odd number of atoms induces a weak ferromagnetic exchange interaction, whereas a bridge with an even number of atoms supports a weak antiferromagnetic exchange interaction, as observed in pure organic compounds and also, as in this case, in metal–organic compounds with an active spin polarization effect. Bridge over Cu–Gd: Observation of ferromagnetic Cu–Gd exchange interactions through one‐ and three‐atom bridges and of antiferromagnetic Cu–Gd exchange interactions through two‐atom bridges is consistent with an active spin polarization mechanism in Cu–Gd complexes (see figure).